Juvenile hyaline fibromatosis in siblings - Valkodai Ramanathan Ravikumar; Ram Ganesh Veerappan Ramamoorthi; Sivakumar Manisankar (Wolters Kluwer Medknow Publications, 2019)
Background: Juvenile Hyaline Fibromatosis is a rare autosomal recessive connective tissue disorder. Case Characteristics: Three year old girl with multiple facial nodules, gingival hypertrophy and multiple joint contractures. Her sibling, male child also had similar findings which was progressive and he died at 2 years. Outcome: Nodule biopsy showed extensively hyalinised dermis with PAS positivity. Message: Juvenile Hyaline Fibromatosis is a differential diagnosis for children presenting with multiple nodular lesions.